2016
DOI: 10.4172/jaa.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Influenza Virus in Lymphocytes Determine by Antiviral Effects of Honey, Ginger and Garlic Decoction

Abstract: Three influenza A virus isolates, one from a human, one from a chicken, and one from a wild bird dropping, were used to infect human peripheral blood mononuclear cells (PBMCs) in culture. The influenza strains were H1N2, H5/H7-N1/N2 (mixture) and H9N2, respectively and were assessed in vitro in human PBMCs in the presence of Phytohemagglutinin (PHA). Viral replication was estimated by visual cytopathic effect (CPE). H1N2 CPE included budding of lymphocytes, fusion of infected cells with neighboring lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Honey in general, and particularly Manuka honey, had potent inhibitory effects against the influenza virus ( Watanabe et al, 2014 ). Profound, in vitro antiviral activity of a mixture of natural honey, ginger and garlic extracts against various strains of influenza virus was observed, moreover they showed in their study that this mixture promotes the proliferation of human lymphocytes ( Vahed & Batool Jafri 2016 ).…”
Section: Antiviral Activity Of Honeybee Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Honey in general, and particularly Manuka honey, had potent inhibitory effects against the influenza virus ( Watanabe et al, 2014 ). Profound, in vitro antiviral activity of a mixture of natural honey, ginger and garlic extracts against various strains of influenza virus was observed, moreover they showed in their study that this mixture promotes the proliferation of human lymphocytes ( Vahed & Batool Jafri 2016 ).…”
Section: Antiviral Activity Of Honeybee Productsmentioning
confidence: 99%
“… Types of Honey/compound Target virus References Manuka and Clover honey Varicella Zoster virus (VZV, the cause of chicken pox and shingles) ( Shahzad and Cohrs, 2012; P . Zareie, 2011 ) Honey and thyme extract Respiratory Syncytial Virus ( Feás and Estevinho, 2011 ) Manuka, buckwheat, honeydew and acacia honeys Influenza virus ( Watanabe et al, 2014b ) Manuka, Honeydew and Rewarewa honeys Rubella virus ( Littlejohn, 2009 ) adenovirus and herpes simplex virus Multi-floral honey from UAE Herpes simplex virus and rubella virus ( Al-Waili, 2004 ) Honey and Royal Jelly Herpes simplex virus type 1 (HSV-1) ( Hashemipour et al, 2014 ) Mono-floral Iranian honey HIV-1 ( Behbahani, 2014 ) Type 1 herpes simplex virus ( Ghapanchi et al, 2011 ) New Zealand medical grade kanuka honey Herpes simplex virus ( Semprini et al, 2019 ) Honey, Ginger and Garlic Decoction Influenza Virus ( Vahed and Batool Jafri, 2016 ) MGO (methylglyoxal) a major component of Manuka Honey Foot and mouth disease virus influenza B viruses; ( Ghizatullina, 1976 )( Charyasriwong et al, 2016 ) Tualang honey (Malaysian multi-floral jungle honey) Common cold ( Sobhanian et al, 2014 ) Reduction of virus load in AIDS patients ( Wan Yusuf et al, 2019 ) Phenols and bioflavonoids found in honey Virus families such as retroviridae, hepadnaviridae, hespervirides, HIV virus, influenza virus, herpes simplex virus, dengue virus, polio virus etc ( …”
Section: Antiviral Activity Of Honeybee Productsmentioning
confidence: 99%
“…Another study has shown that honeys including Manuka, Soba, Kanro, Acacia, and Renge have antiviral effects, and Manuka honey is the most potent antiviral candidate against influenza virus A/WSN/33 (H1N1) in the cultured Madin–Darby canine kidney (MDCK) cell line [ 29 ]. Moreover, extracts of honey, garlic, and ginger (HGG) mixture showed antiviral activity against influenza A virus isolates and is comparable to the standard antiviral drug Amantadine [ 57 ]. This in vitro study showed that HGG inhibited H1N2 replication in human peripheral blood mononuclear cells (PBMCs) and promoted cellular proliferation [ 57 ].…”
Section: The Medicinal Properties Of Honeymentioning
confidence: 99%
“…Moreover, extracts of honey, garlic, and ginger (HGG) mixture showed antiviral activity against influenza A virus isolates and is comparable to the standard antiviral drug Amantadine [ 57 ]. This in vitro study showed that HGG inhibited H1N2 replication in human peripheral blood mononuclear cells (PBMCs) and promoted cellular proliferation [ 57 ].…”
Section: The Medicinal Properties Of Honeymentioning
confidence: 99%
See 1 more Smart Citation